Metropolis mapping the city - Black, Jeremy 1955- (Bloomsbury, 2015)
This sumptuous volume looks at the development of the city map through time, revealing how we organize the urban space, from skyline profiles, bird's eye views and panoramas, to the schematic maps of transport networks and road layouts to help us navigate, and statistical maps that can provide information on human aspirations.